Association between physical activity, learning style, and academic performance among UTAR health science undergraduates - Yeoh, Zhe Yi (2022)
Background and Objective: Eastern and Western education systems have been compared due to their ideological difference which contrasts with each, in terms of learning. Eastern learners were found to struggle in their academics with concomitant stress, which was attributed to their learning way of rote memorization with a feeling of meaningless learning. This struggle was pronounced among health science students. As a coping method, physical activity (PA) and learning style (LS) are the potential mediators for the students to improve their academic performance (AP). In the event of PA, the volume of the hippocampus and brain cortical blood flow are increased and, thereby activating the brain for improving learning. Previous studies found that students learn better when education or self-learning material is delivered to suit their LS. Thus, this study aims to identify PA level and LS preference, and their relationship with academic performance among health science undergraduates at Universiti Tunku Abdul Rahman (UTAR) in Malaysia. Methods: Cross-sectional study design is adopted in this study. The study population recruits UTAR health science undergraduates in Malaysia. International Physical Activity Questionnaire – Short form (IPAQ-SF) and Honey and Mumford’s Learning Style Questionnaire (LSQ) – 40 items are used to evaluate PA level and LS respectively. AP is assessed by self-reported CGPA. Results: Out of 202 participants, the majority of moderate PA level (39.1%) followed by high PA level (32.2%) was identified. Male (50%) was likelier to have high PA level than female (23.1%). Normal BMI (33.3%) was the highest proportion in those with low PA level. For LS, the majority with a single preferred style (66.9%) was notable in this study. Reflector style (30.3%) was the predominant LS among them. The activist style was shown to have the iii highest proportion with a very strong preference (8.9%). Furthermore, there is no association between PA and AP. In LS, only the pragmatist score found a weak and negative association with AP (r = - 0.156, p-value = 0.027) whereas other LS found none. Conclusion: There is high prevalence of moderate PA level among UTAR health science undergraduates. With a majority of single preferred LS, the reflector style is the dominant LS preferred by them. PA found no association with AP. However, the pragmatist style has weak and negative association with AP. Hence, PA and LS are not the determinants of AP, and those with pragmatist style, developing other LS is encouraged. Further investigation on determinants of improving academic performance could be established in order to find out the possible mediators for helping those students who struggle academically.